The Effect of Competence, Individual Characteristics and Locus Of Control On Employee Performance At The Secretariat Of Pariaman City DPRD - Rofika, Rofika; Susanti, Febsri (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine the influence of competence, individual characteristics and the lacus of control partially and simultaneously on employee performance at the Pariaman City DPRD secretariat. Samples were selected using the total sampling method. The sample in this study was 40 employees of the Pariaman City DPRD Secretariat. Data collection techniques using questionnaires, while data analysis methods use validity and reliability tests, classical assumptions, multiple linear regression analysis and statistical tests (t test, F test and coefficient of determination). The results showed that the competency variables affected employee performance at the Pariaman City DPRD secretariat, with a calculated value of 3.739 > ttable 2.021 at a significant level of 0.001 < 0.05. So it can be concluded that H1 was accepted, the results of the study showed that individual characteristic variables affect the performance of employees at the Pariaman City DPRD secretariat, with a calculated value of 3.577 > ttable 2.021 at a significant level of 0.001 < 0.05